Comparing the effectiveness of a multi‐component weight loss intervention in adults with and without intellectual disabilities. Issue 1 (27th March 2013) - Spanos, D.; Hankey, C.; Boyle, S.; Melville, C.
Abstract Background The prevalence of obesity in adults with intellectual disabilities (ID) is rising, although the evidence base for its treatment in this population group is minimal. Weight management interventions that are accessible to adults with ID will reduce the inequalities that they frequently experience in health services. This short report compared the effectiveness of weight management in those with and without ID who completed nine sessions of a multi‐component weight management programme. Methods TAKE 5 is a 16‐week multi‐component weight management intervention for adults with ID and obesity [body mass index (BMI) ≥30 kg m–2]. This intervention is an adaption of the weight management programme provided by the Glasgow & Clyde Weight Management Service (GCWMS) for adults without ID and obesity (National Health Service based). Fifty‐two participants of the TAKE 5 programme were individually matched by baseline characteristics (sex, age and BMI) with two participants without ID of the GCWMS programme. Comparisons in terms of weight and BMI change and rate of weight loss were made for those who attended all nine sessions. Results There were no significant differences between the groups in the amount of weight loss (median: −3.6 versus −3.8 kg, respectively, P = 0.4), change in BMI (median: −1.5 versus −1.4 kg m–2, P = 0.9), success of achieving 5% weight loss (41.3% versus 36.8%, P = 0.9) and rate of weight loss across the 16‐week intervention. Conclusions A multi‐component weight loss intervention can be equally effective for adults with and without ID and obesity.